Botanical Medicine in Clinical Practice 2008
DOI: 10.1079/9781845934132.0031
|View full text |Cite
|
Sign up to set email alerts
|

Arab herbal medicine.

Abstract: Despite the great progress in modern medicine, traditional medicine has always been practised in the Arab-Islamic world. Cultural beliefs and practices often lead to self-care or home remedies in rural areas and consultation with traditional healers. Traditional therapies have been utilized by people in the Mediterranean region who have faith in spiritual healers, homeopaths or even many herbalists. These are the first choice for problems such as infertility, impotence, diabetes, obesity, epilepsy, psychosomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Several studies have revealed that natural products exhibit an extensive spectrum of biological activities such as, stimulation of the immune system, antibacterial, antiviral, anti-hepatotoxic, anti-ulcer, anti-inflammatory, antioxidant, anti-mutagenic, and anti-cancer effects [6,36,66,[84][85][86]. A variety of grains, cereals, nuts, soy products, olives, beverages such as tea and coffee, and spices including turmeric, garlic, ginger, black pepper, cumin and caraway confer a protective effect against cancer [33,35,36,66,85,87].…”
Section: The Wisdom Of the Past Led To The Discovery Of Chemopreventimentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have revealed that natural products exhibit an extensive spectrum of biological activities such as, stimulation of the immune system, antibacterial, antiviral, anti-hepatotoxic, anti-ulcer, anti-inflammatory, antioxidant, anti-mutagenic, and anti-cancer effects [6,36,66,[84][85][86]. A variety of grains, cereals, nuts, soy products, olives, beverages such as tea and coffee, and spices including turmeric, garlic, ginger, black pepper, cumin and caraway confer a protective effect against cancer [33,35,36,66,85,87].…”
Section: The Wisdom Of the Past Led To The Discovery Of Chemopreventimentioning
confidence: 99%
“…One method he discovered was the "Hindiba", (chicorium intybus) an herbal compound drug which Ibn al-Baitar later identified as having anticancer properties and which could also treat other tumors and neoplastic disorders [6,[11][12][13][20][21][22].…”
Section: And It Was Told By One Of the Predecessors That A Physician mentioning
confidence: 99%
See 2 more Smart Citations
“…However, cauterization is contraindicated, if the cancerous tumor has come close to sensitive and vital organs. [9] Collectively it can be summed that black bile plays a pivotal role in the development of cancer. Black bile purgatives play an important role in early stages of cancer therapy.…”
Section: Introductionmentioning
confidence: 99%